Kandungan Zat Kimia Anorganik Pada Beberapa Proses Filtrasi Air Minum Kemasan dan Isi Ulang Menggunakan One-Way Manova - Heruna Tanty (ComTech: Computer, Mathematics and Engineering Applications, 2010)
Analysis of chemical substances in some processes an-organic bottled water and drinking water recharge has been done using One Way Manova. Samples originated from springs Ciburial Bogor taken in May 2009 at 10 depots refill drinking water process (AMDIU) Around Syahdan and Anggrek Campus of Bina Nusantara University. Reserve osmosis filtration processes and filtration Hollow Fiber and testing of heavy metal contents of five CN, Pb, Mn, Cr, and Cd in the company carried out the bottled water (bottled water) PT Buana Cikarang Tirta Abadi. Test results and analysis show that the processed water filtration contains CN, Pb, Mn, Cr, and Cd was lower than that of water filtration was not processed. And drinking water processed by filtration Reserve Osmosis, contains CN, Pb, Mn, Cr, and Cd was lower than that processed by Hollow Fiber Filtration and Granular Activated Charcoal.